PERANCANGAN KENDARAAN BERMOTOR RODA TIGA UNTUK PENYANDANG TUNA DAKSA - Julhija Ema Siputra; Nanang Suffiadi; Fadelan Fadelan; Sudarno Sudarno; Muh Malyadi (Universitas Muhammadiyah Ponorogo, 2022)
Tuna Daksa is a term for individuals who have lost or incomplete body parts that can be seen with the naked eye. One solution to help people with physical disabilities in carrying out daily activities in the field of transportation. Modification of motorized vehicles often lacks safety, especially when used on curvy roads due to lack of balance, so that it is overcome by modifying motorized vehicles using the one-wheel pull method. This method is used to adjust the balance of wheel rotation when turning a corner, and is equipped with parts that can support comfort in its use. The main parameter in this research is the analysis of the spindles and the components of the tools used. The material used to design the axle with bending load only is JIS E4502 class 4 carbon steel qwb = 60 kg/mm and its elongation limit is 30 kg/mm. The feasibility of the design of the modification of the tool is based on the results of research from the calculation that the diameter of the calculation results is above 17 mm, very safe to use and more than 1 mm with the previous diameter of 16 mm.